Microwave shielding properties of Co/Ni attached to single walled carbon nanotubes1. Issue 25 (7th July 2015) - Singh, B. P.; Saket, D. K.; Singh, A. P.; Pati, Santwana; Gupta, T. K.; Singh, V. N.; Dhakate, S. R.; Dhawan, S. K.; Kotnala, R. K.; Mathur, R. B.
<x xml:space="preserve">Abstract</x> Cobalt and nickel nanoparticles attached to single-walled carbon nanotubes were prepared by the dc-arc discharge technique and showed a microwave shielding effectiveness value of 24 dB for a 1.5 mm thick sample in the frequency range 12.4–18 GHz.